Technical trading systems as crystal balls in reducing risk: The Malaysian stock market - Kut Heng, Fred Tham; Noor Azlinna, Azizan; Yeap, Lau Wee (Medwell Journals, 2012)
This study investigates the advantage of technical analysis in reducing risk and generates profits and generates greater return than a passive strategy. Researcher examine the mean returns of 13 technical trading systems against the returns from a buy and hold strategy for the 7 year period from 1996-2009 for Malaysian stocks. The 13 technical trading systems are 1-30 dual simple moving average crossover, 5-20 dual simple moving average crossover, 3-7 exponential moving average crossover, Relative Strength Index (RSI), momentum, stochastic, Moving Average Convergence Divergence (MACD), five Channel Breakout Systems (CBO 20-20, CBO 20-10, CBO 20-5, CBO 10-5 and CBO 15-5) and the Directional Movement Index (DMI). The findings reveal that 12 out of 13 trading systems produced significantly positive gross returns when no transaction costs were involved. These findings refute the assertion that Malaysian stock prices are weak-form efficient suggesting that technical trading systems can be exploited to make abnormal profits.